National webinar for scientific writing training - Nurul Huda; Detson Ray Halomoan Sitorus; Budiman Baso (Universitas Muhammadiyah Magelang, 2022)
According to the 2019 OECD survey, Indonesia ranked 62 out of 70 countries in terms of literacy levels. The purpose of the community service is to provide motivation, knowledge, and skills to participants in the field of scientific writing. A web seminar for scientific writing training, which held online on November 13, 2021 and attended by 384 people, used as program method. According to the feedback, the implementation of the webinar training for scientific writing, 92.2% of participants said they were motivated to write scientific papers, and 96% said they could write scientific papers properly and correctly.